Health information analysis of cryptorchidism-related short videos: Analyzing quality and reliability - Yuqiang Sun; Xingjian Liu; Xintao Zhang; Qiongqian Xu; Aiwu Li (Digital Health)
Objective Cryptorchidism is a common congenital anomaly in children. Short video content has increased awareness and urged timely intervention, but there is a lack of understanding about the quality and reliability of these videos. This survey assesses the quality and credibility of cryptorchidism-related videos on Chinese short video platforms to ensure accurate information for caregivers and healthcare professionals. Methods We analyzed 228 videos from TikTok, Bilibili, and Kwai on 16 May 2024. Using the Journal of the American Medical Association (JAMA) criteria, Global Quality Score (GQS), and modified DISCERN score, we evaluated the videos based on six factors: definition, risk factors, symptoms, tests, treatment, and outcome. Results Video quality varied significantly across platforms ( P  = .03). Medical professionals’ videos had higher JAMA scores than those by nonmedical professionals ( P  < .001), but no significant differences were found in GQS ( P  = .633) or modified DISCERN scores ( P  = .853). Overall, video quality was suboptimal, focusing mainly on treatment, symptoms, and prognosis, while neglecting tests and risk factors. Longer videos correlated with higher GQS ( r  = .34, P  < .001) and modified DISCERN scores ( r  = .39, P  < .001), while newer videos were of higher quality (GQS: r  = −.19, P  < .005; modified DISCERN: r  = −.25, P  < .001). Higher engagement (comments: r  = −.16, P  = .01; shares: r  = −.18, P  = .04) was associated with lower quality. Conclusion Overall, the videos’ quality and reliability were moderate, with professional content providing more accurate insights. This highlights the need for improved regulation of medical information on short video platforms.